2019
DOI: 10.1289/ehp4094
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Particulate Matter Exposure and Onset of Depression in Middle-Aged Men and Women

Abstract: Background:Long-term exposure to particulate matter (PM) air pollution is associated with all-cause mortality and adverse cognitive outcomes, but the association with developing depression remains inconsistent.Objective:Our goal was to evaluate the prospective association between PM air pollution and developing depression assessed using the Center for Epidemiological Studies Depression (CES-D) scale.Methods:Subjects were drawn from a prospective cohort study of 123,045 men and women free of depressive symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…20 21 One other cohort from South Korea also found no association between exposure to PM 2.5 and depression. 22 Of the three European cohorts, one was Finnish. However, it was different from this study in terms of setting, study years, outcome definition and exposure modelling.…”
Section: Discussionmentioning
confidence: 99%
“…20 21 One other cohort from South Korea also found no association between exposure to PM 2.5 and depression. 22 Of the three European cohorts, one was Finnish. However, it was different from this study in terms of setting, study years, outcome definition and exposure modelling.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Studies conducted in Barcelona (Vert et al, 2017), south Korea (Kim et al, 2016), and China (Gao et al, 2017;Qiu et al, 2019;Song et al, 2018;Wang et al, 2018;Xue et al, 2019) also found the increase of PM2.5 concentrations is associated with the risk of mental disorder morbidity. However, the evidence is still mixed as some other studies conducted in many parts of the world showed no association between particulate matter and MDs (Chen et al, 2018a;Tong et al, 2016;Wang et al, 2014;Zhang et al, 2019). For instance, a study based on four European general population cohorts found no association between PM2.5 and depression (Zijlema et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Psychosocial stress can manifest in many forms, such as perceived stress, anxiety, or depression, and it has been reported that air pollution is associated with perceived stress 12 , mood 13 , suicide 14 , symptoms of depression 15 and anxiety 16 , psychiatric emergency room visits 17 , and mental health disorders, as summarized in a meta-analysis 18 . Perceived stress is widely assessed using the Perceived Stress Scale (PSS; a measure of global stress), in which situations are appraised by individuals as stressful 19 .…”
Section: Introductionmentioning
confidence: 99%